"Atsi ... excludat matrimonii essentiale aliquod elementum": rechtssystematische Überlegungen zu einem unbestimmten Begriff des c. 1101 § 2 - Zotz, Bertram (Zeitschrift für katholische Theologie, 1996)
C 1101 § 2 declares the nullity of marriage "if, however, either or both of the parties should by a positive act of will exclude [...] any essential element of marriage [...]", but it does not speak about the objects affected by the exclusion. The following considerations try to give a systematical clarification of this question of law by critical recognition of proposed solutions that have been worked out till now. Proceeding from the not only personal but also juridical view of marriage of the Second Vatican council which leads to the juridical understanding of marriage as a totality of different mutual rights and duties, the "elementa essentialia matrimonii" will be understood as those rights and obligations that constitute the essence of the contract. Their contents are determined by the really aimed objects that follow from the in c. 1055 § 1 mentioned aims of marriage and its essential properties.